Treatment of industrial effluent to reclaim copper using adsorption technique. Issue 3 (4th July 2022) - Bawkar, Shilpa Kalamani; Choubey, Pankaj Kumar; Parween, Rukshana; Panda, Rekha; Singh, Pramod Kumar; Jha, Manis Kumar; Lee, Jae-chun
ABSTRACT: Effluent generated during metal finishing in industries contains large amount of heavy metals, which get discharged into water bodies and creates environmental pollution as well as loss of metal values. Present studies report the adsorption of copper (Cu) from the effluent using Tulsion T-42 resin. Experiments were carried out for the adsorption of Cu from the effluent of Chemical and Mechanical Polishing (CMP) industries using cationic resin Tulsion T-42 (adsorbent). To get the optimized adsorption condition for copper the studies were carried out with varying process parameters i.e., contact time, adsorbent dose, pH, etc. Result of the batch experiments shows that 95% copper was adsorbed from the effluent containing 100 ppm copper using 0.1 g Tulsion T-42 in 50 mL feed solution at pH 4.0 in contact time of 30 min. The obtained data from Cu adsorption studies fitted well with Freundlich adsorption isotherm and followed second-order rate reaction. The 99% copper was found to be eluted from loaded adsorbent using 10% sulfuric acid in 60 min contact time. FT-IR result confirmed that complex with active sulphonic group of Tulsion T-42 was formed. The findings of the studies will be useful for the reclamation of copper from the waste water of metal finishing industries.